The role of Kurdsat Kurdwari in preserving Kurdish cultural identity - Latif, Asst.L. Derya Abdel Wahab; Saado, Dr. Kovan Hussein (Sulaimani Journal for Humanities, 2025)
There is a complex and multifaceted relationship between culture and media. Media can serve as a vehicle for cultural dissemination, facilitating the importation of foreign cultural elements and, in some cases, contributing to the erosion of indigenous cultural identities. Conversely, media can function as a custodian of national culture, safeguarding and reflecting the various dimensions of a nation’s cultural identity. The Kurdish people possess a rich cultural heritage; however, due to historical repression and geopolitical fragmentation, they have encountered significant challenges in preserving their cultural identity. This study seeks to critically examine the role of television programs in maintaining and promoting Kurdish cultural heritage, analyzing how media can either protect or undermine local cultural traditions. While contemporary television content often acts as a conduit for foreign cultural influences—potentially diluting native traditions—certain programs are dedicated to the preservation of local culture. This research investigates television programs that actively promote Kurdish cultural identity through the integration of indigenous cultural materials and traditions. A descriptive research design was employed, utilizing a survey-based methodology. The study was conducted at Sulaimani Polytechnic University – Sulaimani Technical Institute, with a randomly selected sample representing the research population. Key Findings: 1-Kurdish television channels, particularly Kurdsat, attract a substantial audience in comparison to other Kurdish media outlets. This channel demonstrates a strong commitment to national and cultural issues through its programming. 2- Kurdsat Kurdwari has played a pivotal role in preserving Kurdish cultural identity by introducing younger generations to traditional cultural elements, thereby ensuring the continuity and preservation of Kurdish heritage. Key recommendations: 1- Increasing the use of Kurdish satellite channels to promote Kurdish culture by producing more high-quality programs focused on Kurdish cultural topics. 2- Encouraging Kurdsat Broadcasting corporation to produce more programs on Kurdish cultural themes, enabling it to take the lead among other channels in preserving Kurdish culture and national identity.
Keywords: Tvprogram; Kurdsat Kurdawari; preserving; culture